Hanukkah bear - Kimmel, Eric A. (Holiday House, 2013)
On the first night of Hanukkah, Old Bear wanders into Bubba Brayna's house and receives a delicious helping of potato latkes when she mistakes him for the rabbi. Includes a recipe for latkes.